Growth differentiation factor-15 as a modulator of bone and muscle metabolism - Hong, Seok Woo; Kang, Jeong-Hyun (Frontiers in Endocrinology, 2022)
This study aimed to clarify potential role of Growth differentiation factor-15 (GDF-15) as a myokine in bone metabolism and muscle function in females with osteoporosis. In total, 45 female participants (71.0 ± 8.5 years) with distal radius fractures were recruited. Participants were classified as healthy/osteopenic participants (n = 28) (CON) or osteoporotic participants (n = 17) (OP) according to their T-score from areal bone mineral density (aBMD) of the femoral neck. Body mass index, upper arm and calf circumferences, and handgrip strength were assessed. aBMD of the total hip, femoral neck, and lumbar spine was measured via dual-energy x-ray absorptiometry. 3D reconstructed computed tomographic images were used to evaluate focal bone quality of the distal radius. Serum levels of GDF-15, insulin-like growth factor-1, and inflammatory markers including tumor necrosis factor-α (TNF-α), interleukin-6, and interleukin-1β, as well as their mRNA levels in the pronator quadratus muscle were determined. Participants in the OP had higher serum GDF-15 level than that in the CON. The mRNA levels of GDF-15, IL-1β, and TNF-α in the pronator quadratus muscle were significantly higher in the OP than in the CON. Levels of both serum GDF-15 and GDF-15 mRNA in muscle were positively correlated with age and negatively associated with aBMD of the total hip and focal bone quality of the distal radius. Grip power was not correlated with circulating GDF-15 levels, but was correlated with circumferences of the upper arm and calf, and levels of GDF-15 mRNA in muscle specimens. The mRNA levels of GDF-15 were correlated with those of inflammatory cytokines such as TNF-α and IL-1β. The mRNA levels of TNF-α were associated with circumferences of the upper arm and calf, and with aBMD of the total hip. The mRNA levels of GDF-15 in muscle were correlated with serum levels of GDF-15 and those of TNF-α. GDF-15 may have potential associations with bone metabolism in humans via paracrinological and endocrinological mechanisms. Maintenance of muscle mass and function would be influenced more by GDF-15 in muscle than by circulating GDF-15. The role of GDF-15 in bone metabolism and muscle homeostasis could be related to inflammatory responses.